Protease-antiprotease balance - Stockley, Robert (Henry Stewart Talks, 2012)
Pathophysiology of COPD and Emphysema, Carl-Bertil Laurell, Alpha 1 antitrypsin deficiency, Effects of neutrophil elastase, Augmentation therapy, Anti inflammatory effects, Testing emphysema progression, Emphysema with normal lung function, Alternative approach for assessing emphysema, The complexity of neutrophil biology, Processes of neutrophil movement, Elastase concentration change, Quantum proteolytic events of neutrophils, Destructive potential of neutrophils, Chemotaxis, Neutrophils and COPD, Monitoring neutrophil elastase activity in vivo, Elastase inhibitors, Role of proteinases in emphysema, The other neutrophil serine proteinases, The smoking mouse, Alveoli in smokers vs. non smokers, Effects of TNF alpha polymorphisms, The roles of MMPs